Thai Airways Restructuring Plan to Avert Bankruptcy - Rupesh Sinha; Navaneetha Kumar; Chinmay Gandre; Rajesh Kumar Nair; Finn Alessandrino; Daisy Mui Hung Kee; Jullia Deol; Khairunraihani Mohd Samuddin; Nor Asyiqin Rosmadi; Rif’atul Muna; A.A. Gde Satia Utama (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
For the past ten years, Thai Airways International Public Company Limited (THAI) has been suffering successive losses year after year. In 2014, THAI implemented a restructuring plan to improve its revenue streams, yet to no avail as it has been reporting losses. This study aims to determine the impacts of the restructuring plan on profitability ratios in the company and to determine which variable contributes the most towards their profits or losses. The data used were THAI financial statements of 2010 to 2019. As the results show, THAI's profitability ratios show no significant changes before and after the implementation of the restructuring plan, and the largest contributors to their losses are fuel and oil expenses and impairment losses of aircraft.